Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

factorization of 8a³ + 27b³ + 64c³ - 72 abc ??

As the first three terms seem to be cubes of 2a, 3b, 4c respectively, we can use the formula

(x+y+z)³ = x³ + y³ + z³ + 3x² (y+z) + 3y² (z+x) + 3z² (x+y) + 6xyz

So x³ + y³ + z³ = (x+y+z)³ - [ 3x² (y+z) + 3y² (z+x) + 3z² (x+y) + 6xyz ]

8a³ + 27b³ + 64c³

= (2a+3b+4c)³ - [ 3 4a² (3b+4c) + 3 9b² (4c+2a) + 3 16c² (2a+3b) + 6 2a 3b 4c ]

= (2a+3b+4c)³ - [ 12a² (3b+4c) + 27b² (4c+ 2a) + 48c² (2a+3b) + 144 abc ]

8a³ + 27b³ + 64c³ - 72 abc =

=(2a+3b+4c)³ - [36a²b+48a²c+108b²c+54b²a+96c²a+144c²b+144abc]-72abc

=(2a+3b+4c)³-[(36a²b+48a²c+72abc)+(108b²c+54b²a+72abc)+(96c²a+144c²b+72abc)]

= (2a+3b+4c)³-[12a(3ab+4ac+6bc)+18b(6bc+3ba+4ac)+24c(4ca+6cb+3ab)]

= (2a+3b+4c)³- [12a+18b+24c] [3ab+4ac+6bc]

= (2a+3b+4c) [ (2a+3b +4c)² - 6(3ab+4ac+6bc) ]

= (2a+3b+4c) [ 4a²+9b²+16c²+12ab+24bc+16ac -18ab -24ac -36bc]

__ = (2a+3b+4c) [ 4a²+9b²+16c²-6ab -12bc - 8ac] __

As the first three terms seem to be cubes of 2a, 3b, 4c respectively, we can use the formula

(x+y+z)³ = x³ + y³ + z³ + 3x² (y+z) + 3y² (z+x) + 3z² (x+y) + 6xyz

So x³ + y³ + z³ = (x+y+z)³ - [ 3x² (y+z) + 3y² (z+x) + 3z² (x+y) + 6xyz ]

8a³ + 27b³ + 64c³

= (2a+3b+4c)³ - [ 3 4a² (3b+4c) + 3 9b² (4c+2a) + 3 16c² (2a+3b) + 6 2a 3b 4c ]

= (2a+3b+4c)³ - [ 12a² (3b+4c) + 27b² (4c+ 2a) + 48c² (2a+3b) + 144 abc ]

8a³ + 27b³ + 64c³ - 72 abc =

=(2a+3b+4c)³ - [36a²b+48a²c+108b²c+54b²a+96c²a+144c²b+144abc]-72abc

=(2a+3b+4c)³-[(36a²b+48a²c+72abc)+(108b²c+54b²a+72abc)+(96c²a+144c²b+72abc)]

= (2a+3b+4c)³-[12a(3ab+4ac+6bc)+18b(6bc+3ba+4ac)+24c(4ca+6cb+3ab)]

= (2a+3b+4c)³- [12a+18b+24c] [3ab+4ac+6bc]

= (2a+3b+4c) [ (2a+3b +4c)² - 6(3ab+4ac+6bc) ]

= (2a+3b+4c) [ 4a²+9b²+16c²+12ab+24bc+16ac -18ab -24ac -36bc]